Evaluating the Lower Urinary Tract Syndrome with a Telemedicine Application: An Exploration of the Electronic Audiovisual Prostate Symptom Score - Liu, Ziyu; Guan, Zhiyuan; Lan, Hongyu; Zhao, Yan; Ye, Zhiming; Lv, Daojun; Yu, Qingfeng; Wang, Ming; Peng, Kaoqing; Fu, Nanfei; Mazzon, Giorgio; Gu, Di (Frontiers in Surgery, 2022)
Background: Visual Prostate Symptom Score (VPSS) assigned by General practitioners (GPs) doesn’t seem to reflect adequately the patient’s lower urinary tract symptoms (LUTS). This may lead to misestimations. We developed an electronic audiovisual version of VPSS (EPSS), a new symptom scale based on a tele-medicine light App. The aim of this study is to explore the usage of this new EPSS. Methods: Male patients aged between 50 and 80 years old accepted to participate in the study and were finally included across 24 community-based health care facilities in Guangzhou, China. Patients were asked to complete Chinese version of VPSS (printed by Astellas Pharma Inc.) and the EPSS before consulting the urology specialists. Patients were divided into two groups based on age. First, we analysed the rate of full-understanding level of EPSS using the chi-square test. Then we analysed the difference between each score of EPSS, VPSS and specialists’ evaluation outcome as Reference Score (RS). Finally, the outcomes were analysed with the Spearman test and Bartlett test separately. Results: 79 male patients were included (mean age 70.42 years). Patients were divided into 2 groups: group 1(aged >70, n=40) and group 2 (aged < 70, n=39). The fully understanding rate in group 1 and 2 were 50% and 64.1%. No significant difference in fully understanding rate (P=0.206) between groups. T test was presented between each question of VPSS, EPSS and RS. All questions didn’t display significant differences (P>0.05), indicating that the total score of three scales have no significant difference in evaluating LUTS. We further explored the variations of choices made by patients in different scales. Spearman’s test among VPSS, EPSS and RS showed positive correlation, coefficients of the total score were 0.92, 0.91 and 0.93 (P < 0.05). Conclusion: EPSS can be comprehended and accepted in a portion of people and showed significant correlation with the VPSS and the urology specialist assessment. Moreover, the sensitivity and advantage to some of the questions is better than VPSS. The results indicated that EPSS could be another choice for both patients and GPs monitoring LUTS, especially during the COVID-19 pandemic.